The European community and SAARC - Lall, K. B., 1915-; Chopra, H. S. 1932-; Meyer, Thomas, 1943- (New Delhi : Radiant Publishers, 1993)
Revised version of papers contributed to a seminar on "European Union in 1992: its Significance for India and South Asia" organized by the West European Division of the School of International Studies, Jawaharlal Nehru University, New Delhi, in September 1990.
Includes index.
Includes bibliographical references.
Newaz
Keywords: European Economic Community -- Congresses; South Asian Association for Regional Cooperation -- Congresses